Initial treatment of transplant-eligible patients in multiple myeloma. Issue 1 (February 2014) - Rosiñol, Laura; Kumar, Shaji; Moreau, Phillipe; Cavo, Michele
<x xml:space="preserve">Abstract</x> Induction therapy followed by intensification with ASCT is the standard of care in younger patients with multiple myeloma. Three-drug induction regimens combining novel agents (VTD, VRD, VCD, PAD) have shown a high CR rate both, pretransplant and posttransplant. Patients with high-risk cytogenetics continues to have an inferior outcome even when treated with novel agents. The role of tandem autologous stem cell transplant (ASCT) is not well established, although some studies show a better outcome with tandem ASCT as compared to single auto. The high response rate obtained with novel agents also raises the question if autologous transplant has a role in front-line therapy or if it should be used as savage therapy after relapse.